Review and Outlook of the Development Course of Intelligent Optical Networks：from ASON to PCE and then to SDON - Nan Hua; Xiaoping Zheng (Dianxin kexue)
The feature and performance of the representative optical network architectures were reviewed，and a novel PIONEER architecture that combines their advantages was proposed.Finally，programmable，scalable and upgradable software defined optical network（SDON）architectures were proposed for future optical networks.